Role of probiotics and synbiotics on inhibiting Streptococcus mutans level in saliva of children: A randomized controlled trial - Vinola Duraisamy; P R Geethapriya; C Bharath; R S Niveditha; J Baby John (Journal of Indian Society of Pedodontics and Preventive Dentistry, 2021)
Background: Probiotics and synbiotics through its direct and indirect interactions interferes with biofilm formation, competes with oral microorganisms thereby creating better oral health. Aim: This study aims to assess the effectiveness of Probiotics and Synbiotics on inhibiting Streptococcus mutans level in saliva of children after 15 days of daily intake of probiotic and synbiotic curd. Methodology: A double-blind randomized controlled trial was planned. Salivary samples at baseline were collected from forty children in the age group of 6–12 years who were divided into two groups of 20 each to receive probiotic and synbiotic curd respectively for 15 days. Salivary samples were collected after intervention and S. mutans levels were estimated. Statistical Analysis: The collected data were analyzed using Statistical Package for Social Sciences (SPSS) version 22. Intra- and inter-group comparison of mean S. mutans levels for both the groups were done using the paired and unpaired t-test respectively. The statistical significance was set at P ≤ 0.05. Results: A statistically significant reduction in salivary S. mutans counts was observed in both the groups after 15 days (P < 0.001). A significantly higher inhibition of S. mutans growth was present in the probiotic compared to synbiotic group (P < 0.001). Conclusion: Probiotics and Synbiotics were effective in inhibiting salivary S. mutans level of children. However, inhibition of S. mutans growth was found to be better in children who consumed Probiotic curd than the Synbiotic curd.